PENGARUH KUALITAS LAYANAN (SERVICE QUALITY) TERHADAP LOYALITAS MELALUI KEPUASAN PADA MAHASISWA UNIVERSITAS NU SURABAYA - Verriana, Rusdyana Intan; Anshori, Mohamad Yusak (UNUSA Press, 2017)
The aim of this research to examine are there impact of service quality to loyalty with satisfaction as intervening variable to students in Nahdlatul Ulama University of Surabaya. Population in this research are students in Nahdlatul Ulama University of Surabaya total of the sample are 368 from 4.536 students. This research are quantitative method with spread 368 questionnaires. The technique analyze of this research use SEM – PLS (partial least square) software. Free variable of this research is service quality (X), intervening variable is satisfaction (Z) and bunch variable is student’s loyalty (Y). The result of this research shown that service quality (X) have positive impact and significant to students loyalty (Y) have positive impact and significant with path coefficient 0,67 with p – value < 0,001 (significant on 1%). While service quality (X) have positive impact and significant to students loyalty through satisfaction variable (Z) shown positive impact and significant with path coefficient 0,47 with p - value < 0,001 ( significant on 1%).